Bifidobacteria Strain Typing by Fourier Transform Infrared Spectroscopy - Deidda, Francesca; Bozzi Cionci, Nicole; Cordovana, Miriam; Campedelli, Ilenia; Fracchetti, Fabio; Di Gioia, Diana; Ambretti, Simone; Pane, Marco (Frontiers in Microbiology, 2021)
Fourier Transform Infrared (FTIR) spectroscopy, a technology traditionally used in chemistry to determine the molecular composition of a wide range of sample types, has gained growing interest in microbial typing. It is based on the different vibrational modes of the covalent bonds between atoms of a given sample, as bacterial cells, induced by the absorption of infrared radiations. This technique has been largely used for the study of pathogenic species, especially in the clinical field, and has been proposed also for the typing at different subspecies levels. The high-throughput, speed, low cost, and simplicity make FTIR spectroscopy an attractive technique also for the industrial applications, in particular for probiotics. The aim of this study was to compare FTIR spectroscopy with established genotyping methods, PFGE and MLST, in order to highlight the FTIR spectroscopy potential discriminatory power at strains level. Our study focused on bifidobacteria, an important group of intestinal commensals generally recognized as probiotics. Strains belonging to Bifidobacterium longum subsp. longum and Bifidobacterium animalis subsp. lactis were taken into consideration together with some additional type strains. For B. longum subsp. longum, it was possible to discriminate the strains with all the methods used. Although two isolates resulted strictly phylogenetically related, constituting a unique cluster, based on both PFGE and MLST, no clustering were observed with FTIR. For B. animalis subsp. lactis group, PFGE and MLST were nondiscriminatory and only one strain was easily distinguished. On the other hand, FTIR discriminated all the isolates one by one and no clustering was observed. According to these results, FTIR analysis is not only equivalent to PFGE and MLST, but for some strains, in particular for B. animalis subsp. lactis group, it can be also more informative, being able to differentiate strains not discernible with the other two methods, based on phenotypic variations likely deriving from certain genetic changes. The FTIR spectroscopy has highlighted the possibility of using the cell surface as a kind of barcode making possible to trace strains, representing an important aspect in probiotic applications. Furthermore, this work constitutes the first investigation on bifidobacterial strains typing using FTIR spectroscopy.